Karakterisasi Morfologi Tanaman Kopi Rakyat di Pulau Bangka - Kurnia, Silvi; Ropalia, Ropalia; Zasari, Maera (Politeknik Negeri Lampung, 2023)
Coffee is a perennial plant planted on Bangka Island by farmers. Exploration of coffee plants was carried out to see several developed varieties that could be grown on Bangka Island. This study aims to determine the diverse morphological character, phenetic relationship, and variability of folk coffee plants in Bangka. This research was conducted in October 2021-April 2022 in Bangka, Central Bangka and South Bangka. This research was conducted using explorative and descriptive methods. Sampling is carried out randomly to determine the sampling location and data collection. The data from quantitative research were analyzed using variability, while phenetic relationships were analyzed using the UPGMA method (uneweighted pair group method with arithmetic mean) with the NTSYS-pc application (numerical taxonomy software and multivariate analysis system). The results of the analysis of phenetic relationships of qualitative characters resulted in a degree of similarity of coefficients at 53% within coffee of melabun, kota kapur, puput and paku. Analysis of quantitative and combined character phenetic relationships between coffee and puput resulted in a degree of co-efficiency similarity at 25% and 42%. The variability of quantitative character analysis is widespread on plant height and number of flowers per node.